Insulin, insulin-like growth factor I (IGF-I), IGF-binding protein-1, growth hormone, and feeding in the newborn. - Ogilvy-Stuart, A; Hands, S; Adcock, C; Holly, J; Matthews, D; Mohamed-Ali, V; Yudkin, J; Wilkinson, A; Dunger, D (1998)
The relationship between GH, insulin-like growth factor I (IGF-I), IGF-binding protein-1 (IGFBP-1), and insulin may be critical to the understanding of variation in early growth, especially in the small for gestational age (SGA) baby. To investigate these relationships, we have undertaken 12-h hormone profiles in 26 babies (13 SGA) at a median of 4.5 days of age. GH levels were measured every 10 min; insulin and IGFBP-1 were measured every 20 min. Mean levels of these hormones and IGF-I levels (from a single sample) were related to size at birth. The GH data were analyzed by Pulsar and time series analysis to characterize hormone pulsatility and relationship with feeds. IGF-I levels correlated with birth weight and length (r2 = 0.47; P = 0.004, and r2 = 0.5; P = 0.0005, respectively, after allowing for gestation), whereas mean GH levels were negatively related to birth size (r2 = -0.18; P = 0.04 and r2 = -0.2; P = 0.03 for weight and length, respectively). No direct relationship between mean GH levels and IGF-I was identified. IGF-I levels were higher in appropriate for gestational age (AGA; mean +/- SD, 82+/-61 ng/mL) than in SGA (34+/-22 ng/mL; P = 0.03) babies. Baseline (mean +/- SD, 25.9+/-11.9), mean (33.9+/-14.0), and peak (45.0+/-18.1 microg/L) GH levels were higher in SGA than in AGA babies [17.1+/-8.2 (P = 0.04), 22.5+/-10.4 (P = 0.03), and 30.7+/-15.4 microg/L (P = 0.04), respectively]. Mean IGFBP-1 levels were also higher in SGA than AGA babies (157.4+/-90.7 vs. 62.7+/-43.8 ng/mL; P = 0.01). A positive correlation was identified between changes in insulin and coincident pulses of GH (r = 0.147; P < 0.01), whereas there was an inverse relationship between insulin and IGFBP-1, with a lag time 120 min (r = -0.33; P < 0.0001). In conclusion, these studies indicate that the GH-IGF-I axis is closely related to feeding in the newborn. In SGA babies, low IGF-I and elevated IGFBP-1 reflect the slow growth, but elevated GH and rapid GH pulsatility may be a signal for lipolysis.